Challenges Faced by Pre-university Students in Excelling STREAM Based Disciplines for a Better Future - Julinamary Parnabas; Mas Afiqah Mohd Azril Razmin; Mugesh Remis; Muhammad Syahmi Naaim Jali; Muhammad Syakir Nabil Mohd Noor; Muhammad Afiq Rafie Ariffin (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan